Sesquiterpene compound α-cyperone relieves the injury in neurons undergoing oxygen-glucose deprivation/reoxygenation (Bangladesh Journal of Pharmacology, 2022)
The present study aimed to explore the effects of α-cyperone, an extract of Cyperus rotundus, on PC12 cells, as well as the underlying mechanism. Following the cells were induced by oxygen-glucose deprivation/reoxygena-tion (OGD/R), the viability, morphology, inflammation, oxidative stress and apoptotic levels in the cells were evaluated. To explore the mechanism of α-cyperone, cells were treated with 3-TYP, a sirtuin-3 (SIRT3) inhibitor, and then the effects of 3-TYP on the function of α-cyperone were assessed. α-Cyperone was found to reduce OGD/R-induced damage to neuronal viability and alleviate inflammation, oxidative stress, and apoptosis. In addition, α-cyperone could elevate SIRT3 and decline acetyl-forkhead box O1 (FOXO1) levels, and 3-TYP broke the effects of α-cyperone on the aforementioned aspects in the PC12 cells. In conclusion, α-cyperone activated SIRT3 and FOXO1 deacetylation, and alleviated OGD/R-induced cell inflammation, oxidative stress, and apoptosis.